Morphological and physiological responses of cowpea (Vigna unguiculata (L) Walp.) cultivars to induced water stress and phosphorus nutrition - Chiulele, Rogerio Marcos (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric) -- University of Stellenbosch, 2003.